Upaya Peningkatan Kemampuan Guru dalam Pemanfaatan Perpustakaan Sekolah Sebagai Sumber Belajar dengan Menggunakan Metode Focus Group Discussion di Sekolah Dasar Negeri 1 Bade Kecamatan Klego Kabupaten Boyolali Tahun Pelajaran 2017/2018 - Sri Dwi Yatmi (Publikasi Indonesia, 2022)
Abstract This study aims to determine the ability of teachers to use the school library as a learning resource in SD Negeri 1 Bade, Klego District, Boyolali Regency. This research is a school action research. The research was conducted at SD Negeri 1 Bade, Klego District, Boyolali Regency. The research subjects were elementary school teachers from class I to class VI. The research procedure uses two cycles. Data analysis techniques using descriptive analysis techniques. The indicator of achievement of the success rate with a minimum score of 75% of teachers shows high activity in participating in Focus Group Discussions for the use of the School Library as a learning resource, at least 75% of teachers give a high response to coaching with the Focus Group Discussion for the use of the School Library as a learning resource and at least 75% of teachers are able to create learning scenarios by utilizing the School Library as a learning resource. The results of this study indicate that through Focus Group Discussions can improve Teacher Ability to Utilize School Libraries as Learning Resources, this is because through Focus Group Discussions they feel that they receive input and know the shortcomings in implementing Utilizing School Libraries as Learning Resources. Based on the results of the study, it can be seen that through Focus Group Discussion, the ability of teachers to use the school library as a learning resource at SD Negeri 1 Bade, Klego District, Boyolali Regency, 2017/2018 Academic Year. Thus, it can be concluded that through Focus Group Discussion can improve the ability of teachers to use the school library as a learning resource at SD Negeri 1 Bade, Klego District, Boyolali Regency.